Answer:
x = 4
y = -3
Step-by-step explanation:
We can use substitution, elimination, or graphically.
Step 1: Rearrange first equation
2x + 4y = -4
2x = -4 - 4y
x = -2 - 2y
Step 2: Rewrite systems of equations
x = -2 - 2y
3x + 5y = -3
Step 3: Substitution
3(-2 - 2y) + 5y = -3
-6 - 6y + 5y = -3
-6 - y = -3
-y = 3
y = -3
Step 4: Find <em>x</em> using <em>y</em>
2x + 4(-3) = -4
2x - 12 = -4
2x = 8
x = 4
Graphically:
Use a graphing calc and analyze where the 2 lines intersect.
The answer is A. I just finished the test.
Answer:
Step-by-step explanation:
you need to cancel out the brackets by multiplying -2.3 with every thing inside the brackets
![-\frac{1}{8}y+24](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B8%7Dy%2B24)
To factor -1/8 out you need to find a number that multiply by -1/8 be equal to each term in the expression.
To find those numbers you divide each term into -1/8:
![\begin{gathered} \frac{-\frac{1}{8}y}{-\frac{1}{8}}=y \\ \\ \frac{24}{-\frac{1}{8}}=-24\cdot8=-192 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B-%5Cfrac%7B1%7D%7B8%7Dy%7D%7B-%5Cfrac%7B1%7D%7B8%7D%7D%3Dy%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B24%7D%7B-%5Cfrac%7B1%7D%7B8%7D%7D%3D-24%5Ccdot8%3D-192%20%5Cend%7Bgathered%7D)
Then, the factors are: